Improving Musical Instrument Workshop to Improve Product Quality of Craftsman in Siponjot Village - Tarigan, Kumalo; Jafar, Fadlin; Gulo, Hubari; Purba, Mauly (Talenta Publisher, 2020)
Workshop is a production house for many craftsmen. Siponjot village has a Silaban Margu studio which produces traditional musical instruments despite the lack of inadequate workshop. The main problem with this workshop is that the production equipment facilities are still inadequate to provide optimal work results. Even by the given limitation, this studio has produced several types of gondang as its work. The excess residual material is generally wasted so that the potential economic value of using the material is immaterialized. The main target of this community service is to empower the people of Siponjot Village. The development of this craft workshop is the provision of creative economic access through the use of material left over from the production of musical instruments into fine arts in the form of handicrafts with economic, artistic and cultural values. This service has provided science and technology transfer while providing increased artistic skills through direct training to the community. It is hoped that in the future the community and craftsmen can take advantage of this potential to form an art-based creative economy in Siponjot Village.